2010
DOI: 10.1007/s11517-010-0692-0
|View full text |Cite
|
Sign up to set email alerts
|

An adaptive gyroscope-based algorithm for temporal gait analysis

Abstract: Body-worn kinematic sensors have been widely proposed as the optimal solution for portable, low cost, ambulatory monitoring of gait. This study aims to evaluate an adaptive gyroscope-based algorithm for automated temporal gait analysis using body-worn wireless gyroscopes. Gyroscope data from nine healthy adult subjects performing four walks at four different speeds were then compared against data acquired simultaneously using two force plates and an optical motion capture system. Data from a poliomyelitis pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
126
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(131 citation statements)
references
References 26 publications
5
126
0
Order By: Relevance
“…Control and Evaluation Detection algorithms based on machine learning and rulebased heuristics are used to identify gait events/phases [6,9,15,[17][18][19][20]. Catalfamo et al [9] evaluated the detection of IC and end of the contact (foot off ) using a single gyroscope on the shank which was validated with seven control subjects walking on level ground and an inclined surface.…”
Section: A Real-time Gait Event Detection For Lower Limb Prosthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Control and Evaluation Detection algorithms based on machine learning and rulebased heuristics are used to identify gait events/phases [6,9,15,[17][18][19][20]. Catalfamo et al [9] evaluated the detection of IC and end of the contact (foot off ) using a single gyroscope on the shank which was validated with seven control subjects walking on level ground and an inclined surface.…”
Section: A Real-time Gait Event Detection For Lower Limb Prosthesismentioning
confidence: 99%
“…Most of the studies were implemented offline with very few real-time data either from the healthy subjects or subjects with motor-control and functional disorders [3,4,9,12,13,17]. Sellas et al [3] reported a MD ± Std of 34 ± 25 ms and 19 ± 36 ms for IC and TO respectively in control subjects and 33 ± 41 ms and 13 ± 38 ms for IC and TO respectively in transtibial amputees.…”
Section: Lack Of Proper Tomentioning
confidence: 99%
See 1 more Smart Citation
“…They exist in one-dimensional as well as multidirectional configurations and are similarly easy to apply as accelerometers. They are often used in combination with accelerometers, magnetic or other sensors and provide estimates for movement of segments in a kinematic chain (Brodie et al, 2008;Greene et al, 2010) using e.g., Kalman filter technique (Luinge & Veltink, 2005). A considerable advantage of this approach is that one can measure full body kinematics in virtually any environment (Cloete & Scheffer, 2010).…”
Section: Accelerometers and Gyroscopesmentioning
confidence: 99%
“…To give some insight onto the best-cited original papers, we selected the top ten from the periods 2008-2009 and 2010-2011. Out of these 20 papers, 7 are in the area of the circulation [8,9,15,20,24,25,27], 7 in the area of rehabilitation including brain computer interface [6,7,11,14,16,17,28], 2 related to sleep [19,35], 2 to tissue engineering and nanotechnology and 2 to electroporation [4,21]. Obviously the distribution of these subjects of publications are somewhat influenced by the special issues we had over this period [2,5,12,18,26,31,32].…”
mentioning
confidence: 99%